Chemical composition and fatty acid profile of Alpine and Saanen goat milk from Bosnia and Herzegovina - Vulić, Ana (Array, 2020)
Interest in the production and sale of goat milk products has been growing over the past 20 years. The chemical composition of goat milk, which greatly affects its nutritional and therapeutic value, makes its products more acceptable to consumers. The aim of this study was to compare the chemical composition and fatty acid profile of Alpine and Saanen goat milk. The results showed that there were differences in certain chemical components between the milk of these two breeds. Protein, fat and ash content in Alpine goat milk was 4.53 g/100 g, 4.65 g/100 g and 0.94 g/100 g, respectively, and these values were higher than in Saanen goat milk (3.64 g/100 g, 3.20 g/100 g and 0.88 g/100 g, respectively). Differences in the fatty acid profile were also observed. Despite being kept under different breeding regimes, no statistically significant differences were observed in the total saturated fatty acids (SFA) or polyunsaturated fatty acids (PUFA) between breeds. Although there was no difference in total SFA content, there was less palmitic acid (C16:0), as the predominant fatty acid in goat milk, in Alpine (26.94 g/100 g of fat) than in Saanen goat milk (28.60 g/100 g of fat). Unlike SFA and PUFA content, differences were observed in total monounsaturated fatty acids (MUFA), with 22.8 g/100 g of fat in Alpine goat milk and 24.0 g/100 g of fat in Saanen goat milk. Based on these findings, it can be concluded that the implemented breeding regimes in different geographical areas with different pasture, together with genetic factors of breeds, greatly affect the goat milk chemical composition and fatty acid profile.